The Influence of Discounts, Free Shipping, and Flash Sales on Purchase Decisions for The Originote Skincare Products on Shopee - Lusiana; Ratnanto, Sigit (Universitas Nusantara PGRI Kediri, 2025)
Abstract (in English) Research aim: The aim of this research is to analyze the influence of discounts, free shipping and flash sales on purchasing decisions. purchase The Originote skincare products on shopee Good in a way separated and also in a way simultaneously . Design/Methode/Approach: This study applies a quantitative approach with a type of research that focuses on causal relationships. The sampling technique involved 40 customers who had purchased The Originote skincare products on Shopee. For data analysis, multiple linear regression tests were used, and data processing was carried out using SPSS version 25. Research Finding: This study shows that discounts, free shipping, and flash sales have a significant influence on purchasing decisions for The Originote skincare products on Shopee. Theoretical contribution/Originality: This study enriches the literature on digital marketing by analyzing the factors that influence purchasing decisions on e-commerce platforms. With a focus on discounts, free shipping, and flash sales, this study provides new insights into how marketing strategies can influence consumer behavior in the digital era. Practitioner/Policy implications: This study provides practical benefits for The Originote company in increasing purchasing decisions for The Originote skincare products on Shopee. Research limitation: This study only focuses on discounts, free shipping, and flash sales as independent variables. However, there are still other variables that can affect the dependent variable and need to be studied further. Keywords: discount, free shipping, flash sale and decision purchase